1999
DOI: 10.1111/j.1475-6803.1999.tb00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Borrowing Relationships, Monitoring, and the Influence on Loan Rates

Abstract: While monitoring borrowers, a bank obtains private information about its customers, giving the bank an informational advantage in the production of subsequent services. Competing theories exist on the way banks use this advantage in the pricing of subsequent services to the customer. If moral hazard limits the transfer of private information, the borrowing relationship transforms into an informational monopoly and can be characterized as a "wasting asset." Alternately, if the banks' competitive environment nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…The evidence that we present is consistent with the notion that more information is generated early in the relationship and with the assertion that asymmetric information creates adverse selection and moral hazard problems in which banks charge high rates initially and reduce rates in later periods after borrower and project characteristics are revealed. Our study results are also consistent with the previous empirical research of Berger and Udell (1995), Blackwell and Winters (1997), Athavale andEdmister (1999), andD'Auria, Foglia, andReedtz (1999). The evidence also suggests that the incumbent bank quickly assimilates private information acquired during the monitoring of loan extensions into loan pricing, a finding that is consistent with the notion that the value of a relationship is not constant over the life of the relationship.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The evidence that we present is consistent with the notion that more information is generated early in the relationship and with the assertion that asymmetric information creates adverse selection and moral hazard problems in which banks charge high rates initially and reduce rates in later periods after borrower and project characteristics are revealed. Our study results are also consistent with the previous empirical research of Berger and Udell (1995), Blackwell and Winters (1997), Athavale andEdmister (1999), andD'Auria, Foglia, andReedtz (1999). The evidence also suggests that the incumbent bank quickly assimilates private information acquired during the monitoring of loan extensions into loan pricing, a finding that is consistent with the notion that the value of a relationship is not constant over the life of the relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Although the literature, exemplified by Rajan (1994, 1995), Harhoff and Körting (1998), Cole (1998), Ongena and Smith (2000), and Houston and James (2001), suggests that relationships do influence the availability of credit, the evidence on the influence of relationships on the price of credit has been mixed. Berger and Udell (1995), Blackwell and Winters (1997), Athavale andEdmister (1999), andD'Auria, Foglia, andReedtz (1999) found that borrowing relationships result in lower loan rates, whereas Slovin and Sushka (1984), Petersen and Rajan (1994), and Degryse and Van Cayseele (2000) found little evidence to support lower loan rates.…”
Section: Sequential Borrowing Relationshipsmentioning
confidence: 99%
“…There have been many papers which treat the determination of a loan interest rate considering default-risk and asset portfolios (e.g., Allen, 1988;Angbazo, 1997;Athavale, 1999;Ho and Saunders, 1981;Ebrahim and Mathur, 2000;Sealey, 1980;Slovin and Sushka, 1983;Wong, 1997;Zarruk and Madura, 1992). However, there have been few papers which study the period of mortgage collection.…”
Section: Introductionmentioning
confidence: 99%
“…This method is used by several authors (Blackwell and Winters, 1997;Charlier, 1998;Harhoff and Körting, 1998;Athavale and Edmister, 1999;Auria et al, 1999) that conclude that a greater concentration of credit with the lender is associated with lower cost of credit, greater access to credit or even more granting credit.…”
Section: Length Of the Banking Relationshipmentioning
confidence: 99%
“…Several studies (Riding et al, 1994;Blackwell and Winters, 1997;Johnson, 1998;Athavale and Edmister, 1999) show that repeated transactions over time between banks and SME contribute to reduce information asymmetry between the parties, diminishing the bank's need to control SME activity and, consequently, it becomes possible for them to obtain an overall improvement in credit terms. Portugal has a bank-based financial system with an undeveloped stock market in comparison with stock markets of USA and other European countries.…”
Section: Introductionmentioning
confidence: 99%